Verification of the main types of conditions of existing taxes in the city of Theofilo Otoni (Research, Society and Development, 2019)
The topographical irregularity of the Teófilo Otoni region is one of the main reasons for the high index of contention use. Considering this factor, a study was carried out to collect data on the types of slope contentions existing in the city of Teófilo Otoni - MG, evaluating the constructive methods, execution and their effectiveness. The focus of the surveys was directed to containments existing in the vicinity of the central area of the city. Technical visits were carried out in several places where there are restraints, thus photographing and cataloging. It was noticed that the use of containment when well executed and of great importance for slope stability, but when aligned with the implantation of an efficient and adequate drainage system for each case. It was also observed that the association of more than one type of containment is particularly important, especially when it is a slope of high altitudes.